2013
DOI: 10.3892/etm.2013.1102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different double-plate fixation methods with olecranon osteotomy for intercondylar fractures of the distal humeri of young adults

Abstract: Although several studies have demonstrated good results with open reduction and internal fixation of intercondylar fractures of the distal humerus, few have specifically addressed the results of such surgical fixation in young adults. The purpose of this study was to compare the clinical outcomes in patients with intercondylar fractures of the distal humerus treated using two different double-plating methods. Twenty-five patients with distal humeral fractures classified as type C according to the Association f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
2
13
0
2
Order By: Relevance
“…Dasheng Tian et al in compared the clinical outcomes of the perpendicular and Y-shaped double-plating with olecranon osteotomy methods when applied to type C distal humerus fractures in young adults and found Mayo Elbow Performance Scores, 84.6% of patients in group I and 83.3% in group II had excellent or good scores. 7 Kilicarslan K et al conducted study on 27 patients and observed the Mayo Elbow Performance Scores to be excellent results in 20 patients (74%), good in 4 (14.8%), fair in 2 (7.4%) and poor in 1 patient (3.7%). 8 Thus the results of our study were comparable to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dasheng Tian et al in compared the clinical outcomes of the perpendicular and Y-shaped double-plating with olecranon osteotomy methods when applied to type C distal humerus fractures in young adults and found Mayo Elbow Performance Scores, 84.6% of patients in group I and 83.3% in group II had excellent or good scores. 7 Kilicarslan K et al conducted study on 27 patients and observed the Mayo Elbow Performance Scores to be excellent results in 20 patients (74%), good in 4 (14.8%), fair in 2 (7.4%) and poor in 1 patient (3.7%). 8 Thus the results of our study were comparable to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The olecranon osteotomy is currently the most widely adopted approach [5,18,22,23,25], and it can prevent the triceps brachii from being severed or split. However, the olecranon osteotomy has more potential complications.…”
Section: Discussionmentioning
confidence: 99%
“…The mean mayo elbow performance score was 82.2 comparable with other studies and signifies excellent results by maintaining functional arc of motion (30° to 110°). [17][18][19][20] Within the last seven years, a two-column theory of the distal humerus anatomy has been advocated whereby the coronal plane of the distal humerus is in the shape of a triangle with the coronoid fossa and olecranon.…”
Section: Discussionmentioning
confidence: 99%